College repercussions on Nursing students' health and lifestyle: an integrative review (Research, Society and Development, 2020)
This aims at clarifying issues regarding nursing students' health and lifestyle by means of an integrative review. Methodology: An integrative review based on the guiding question "How is nursing students' health and lifestyle being addressed in the literature?". The following databases were used: Latin American and Caribbean Literature on Health Sciences, La Medical Literature Analysis and Retrieval System online, Nursing Database, Scopus Content Overview and Web of Science. Results: the sample was comprised of 11 international papers, among them 27.27% are from Colombia; 18.18% are from China and 9.09% are concurrently from Iran, Malaysia, Mexico, Mississippi, London and Turkey. In the first category regarding “Nursing students' unhealthy lifestyle”, sleep decrease was noticed, as well as poor eating habits, stress, depression and anxiety. In the second category concerning "The Nursing college as a promoter for students' health and a healthy lifestyle", the positive interference of health promotion by a critical awareness in individual well-being was highlighted. Conclusion: Both students and college must be protagonists in the promotion of integral health and lifestyle, so that each one can play their role with a positive influence on the standards adopted during Nursery school formation.